The Education of Diverse Student Populations
XII, 281 p.
Keywords: This book takes up the challenge of examining the thorniest educational issue from a global perspective. It contributes to the evidence-based conversation among policy makers, educators, and researchers around the world about what works to improve the education outcomes and what can make a bigger difference for the education of diverse students. The eleven countries included — the United Kingdom, Austria, Canada, the United States, South Africa, Ghana, China, Singapore, Malaysia, Australia, and New Zealand are unique, and yet overlap in the sense that they all face similar challenges of teaching diverse students. The authors, being education and cultural insiders, discuss country-specific policies, efforts, and best practices in the education of diverse students; share stories of success and failure; and explore current best practices from global, social, political, and economic perspectives. Built on previous theories and research, it describes diverse students’ experiences in theglobal and information age, and searches for effective policies and practices that help these students to perform better in school and in life. Readers are forced to step outside of their own experiences and commonly held beliefs about education. Conscious recognition that there are other ways of doing things may result in new approaches that we have not explored before. We hope the insights, lessons, and conclusions drawn from examining this pressing education issue from a global perspective will help nations to better understand and deal with it in their own educational system. Finally, a book that examines the challenges facing today’s educators. The Education of Diverse Student Population: A Global Perspective answers the question of how to cultivate a learning environment for culturally and linguistically diverse students. This book will encourage both inservice and preservice teachers to value the differences that each culture brings to the classroomand view this diversity as an opportunity for teaching and learning with a global focus. Dr. Rosalyn Anstine Templeton, Executive Dean, College of Education and Human Services, Marshall University, Huntington, USA.